Adaptive Strategies of Bali Tourism and Hospitality Enterprises amid COVID-19 (Editorial) - Subadra, I Nengah (Language Assistance, 2024)
This edition of the journal focuses on adaptive strategies in Bali's tourism and hospitality sector during the COVID-19 pandemic. It highlights innovative approaches in marketing, operational policies, digital engagement, and service quality that have been crucial for maintaining resilience and customer loyalty. Key articles discuss the importance of revising marketing strategies, implementing dynamic reservation policies, leveraging digital and relationship marketing, ensuring service quality, and analysing consumer behaviour to optimise performance. The volume offers practical insights on sustaining revenue streams, managing costs, and enhancing team cooperation. The knowledge shared in this volume offers valuable guidance for navigating the ongoing challenges in the hospitality industry.